Grovfoder för dikor - Månsson, Ann-Christin (2010)
This literature review examines different forages which are well suited for suckle cow production in Sweden today. They should also be possible to cultivate in Sweden under the current circumstances. Crops suitable for grazing in Swedish climate but not used in Sweden today, but which may be relevant for Swedish conditions are also mentioned. In Sweden today, mainly grass silage, straw and hay are used as forage, but also wholecrop silage is used to some extent. However, concentrates are not used to a greater extent, since it contains too much energy. The concentrates that are used are oats, barley, rye and triticale. For cows other feeds are also used such as linseed, soybean, pea, broad beans and rapeseed. The alternative forage being investigated is lucerne, corn silage, sunflower silage, straw of peas, by-products of sugar production, turnips and lupine. Grazing crops that can extend the grazing period is lucernes, green fodder rape, sorghum, and turnips.